One Iron Injection Is Not Enough—Iron Status and Growth of Suckling Piglets on an Organic Farm - Katharina Heidbüchel (Animals, 2019)
Suckling piglets cannot satisfy their demand for the essential trace element iron from sows’ milk alone, which is poor in iron. Therefore, iron is usually supplemented by injecting 200 mg iron (as iron dextran) on day 3 post natum. However, the longer suckling period in organic pig herds leads to iron intake from feed starting later. We hypothesized that one iron injection is not enough for organically reared piglets, and that a second and third injection would improve their iron status and growth. On an organically certified experimental farm, 288 piglets from 32 litters were allocated to three treatments with one iron injection on day 3, two injections on day 3 and 14 and three injections on day 3, 14 and 21 post natum, respectively. One injection resulted in the lowest hematocrit and serum iron levels until day 28 post natum and the lowest daily weight gains until weaning, while piglets receiving two or three iron injections did not differ from each other. Based on these observations, we conclude that one iron injection is not enough to ensure adequate iron supply and unimpaired growth of organically reared piglets, and additional iron supply is necessary.